Enhancing Treg persistence by inhibiting necroptosis restrains autoimmune pathology - Qiaoyan Wu; Na Cui; Li Gao; Zhihui Lu; Xiang Ao; Rui Pang; Xingyan Li; Heling Pan; Daichao Xu; Peiying Li; Junying Yuan; Chengyu Zou (Journal of Clinical Investigation, 2026)
Regulatory T (Treg) cells hold great promise as next-generation therapeutics for autoimmune diseases. However, maintaining their functional persistence within inflamed tissues remains a major translational challenge. Using an in vitro system that recapitulates the inflammatory CNS milieu of multiple sclerosis (MS), together with a pooled shRNA screen, we identify necroptotic signaling as a key driver of Treg cell death, thereby compromising Treg functional persistence under inflammatory conditions. We further demonstrate that Treg cells in both a mouse model of MS and patients with MS exhibit a preferential susceptibility to RIPK1 kinase-dependent necroptosis. Mechanistically, a FOXP3-driven low-glucose metabolic program renders Treg cells intrinsically susceptible to necroptosis by limiting O-GlcNAc modification on RIPK1. This vulnerability is not shared by conventional T cells under comparable inflammatory conditions. Finally, in combined with adoptive Treg cell transfer, we show that selective inhibition of necroptosis in Treg cells enhances their survival and suppressive function at sites of active inflammation, thereby reducing autoimmune pathology in mouse models of MS and systemic lupus erythematosus. Together, these findings identify necroptotic cell death as a barrier to Treg persistence within inflamed tissues and highlight the therapeutic potential of necroptosis-resistant Treg cells for the treatment of autoimmune diseases.